Spin Filter Based on EuO Monoxide - Yu. F. Golovnev; D. A. Nurguleev (Известия высших учебных заведений России: Радиоэлектроника)
The basis of spin filter operation is the possibility to obtain different population of states with spins up and down for free electrons. However, in a magnetic macroscopic field, scattering by heavy atoms reduces their population density by 106 times. To obtain the maximum possible degree of spin polarization it is proposed to use ferromagnetic EuO in semiconductor superlattices, e. g. EuO–SrO. The article substantiates the creation of a spin filter based on a superlattice composed of SrO and EuO nanolayers. The scheme of ferromagnetic semiconductor EuO energy levels is demonstrated as well as splitting of 5d EuO levels by crystal field. The position of 4f 7-multiplet and the energy of formation of triplet exciton are determined.